2021
DOI: 10.1080/07317107.2021.1940586
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in Reactions to Tics and Tic Severity

Abstract: The present study used parent-report data to explore crosscultural similarities and differences in tic severity and reactions to tics across 223 children with Tourette's disorder (TD) from the United States, United Kingdom, and Netherlands/Norway. Psychometric properties of the TARS-PR and PTQ were also examined and results indicated that both measures may be suitable for assessing tic severity and the consequences of tics in these countries. No differences in parent-reported tic severity were found. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Our research demonstrated acceptable internal consistency for the PTQ. However, the PTQ showed slightly lower internal consistency in this sample as compared to previous Western-based studies (0.68-0.79 in our study, vs. 0.77-0.92 in studies by Western-based studies)[6][8] [9]. Such variations may be attributable to profound cultural and contextual factors.…”
Section: Reliability Of the Ptqcontrasting
confidence: 90%
See 2 more Smart Citations
“…Our research demonstrated acceptable internal consistency for the PTQ. However, the PTQ showed slightly lower internal consistency in this sample as compared to previous Western-based studies (0.68-0.79 in our study, vs. 0.77-0.92 in studies by Western-based studies)[6][8] [9]. Such variations may be attributable to profound cultural and contextual factors.…”
Section: Reliability Of the Ptqcontrasting
confidence: 90%
“…This cultural perspective, combined with the stigma attached to neurological or psychiatric conditions (e.g., some Chinese parents may fear negative judgments, therefore minimizing or omitting reports of certain behaviors when completing the PTQ) may in uence how tics manifest or are reported[16] [17]. Additionally, cultural perceptions of what constitutes "severity" could vary, impacting the consistency of responses on severity-related items of the PTQ [9]. Parallel to the study by Ricketts et…”
Section: Reliability Of the Ptqmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivating factors for these behaviors include maintaining social normalcy and peer acceptance ( O'Hare et al, 2015 ; Lee et al, 2016 , 2019 ; Malli et al, 2019 ; Soós et al, 2022 ). Unfortunately, many ITS experience peer rejection ( Lee et al, 2016 , 2019 , 2020 ; Lemelson and Tucker, 2017 ; O'Hare et al, 2017 ; Malli et al, 2019 ; Rodin et al, 2021 ; Stiede et al, 2021 ; Soós et al, 2022 ; Stofleth and Parks, 2022 ), the act of being labeled by others or stigmatization ( O'Hare et al, 2015 , 2016 ; Lee et al, 2016 , 2019 , 2020 ; Wadman et al, 2016 ; Edwards et al, 2017 ; Lemelson and Tucker, 2017 ; Jackson et al, 2019 ; Malli et al, 2019 ; Charania et al, 2022 ; Iyanda, 2022 ; Malli and Forrester-Jones, 2022 ; Mataix-Cols et al, 2022 ; Soós et al, 2022 ; Stofleth and Parks, 2022 ; Vermilion et al, 2022 ), loneliness ( Lee et al, 2016 , 2019 ; O'Hare et al, 2017 ; Malli et al, 2019 ; Rodin et al, 2021 ), and internalizing the negative stereotypes or self-stigma ( Eaton et al, 2016 ; Hanks et al, 2016 ; Liu et al, 2017 ; Silvestri et al, 2017 ; Lee et al, 2019 , 2022 ; Malli et al, 2019 ; Malli and Forrester-Jones, 2022 ). These experiences can influence the persistence of moderate-to-severe tics ( Groth, 2018 ) and tic severity ( Shiu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%